Pengaruh Harga Tindakan, Promosi, dan Lokasi Klinik Terhadap Keputusan Konsumen Memilih Klinik Sunat Surgero Tebet Jakarta Selatan - Muhammad Iqbal; Zulkifli Rangkuti; Irawan R. D Budianto (Lembaga Pengembangan Kinerja Dosen, 2025)
This academic study aims to examine the impact of service pricing, promotion, and clinic location on customer decisions in choosing the Sunat Surgero Clinic in Tebet, South Jakarta. The basis of this research stems from the increasing competition among circumcision centers in metropolitan areas, which requires every healthcare provider to understand the key factors shaping customer decision-making. The study employs a quantitative approach through a survey of 100 participants, consisting of clients or their guardians who have previously used the clinic’s services. The research instrument utilized a five-point Likert scale questionnaire to measure respondents’ perceptions of the three examined factors. Data analysis was conducted using the Partial Least Squares (PLS) method through the SmartPLS 4 software to assess the relationships and effects among variables in the research framework. The findings reveal that all three independent variables—service price, promotion, and clinic location—have a positive and significant influence on customer decisions. The path coefficients indicate the influence of service price (β = 0.286; p = 0.025), promotion (β = 0.281; p = 0.032), and clinic location (β = 0.233; p = 0.030). These results suggest that pricing aligned with service quality, effective and engaging promotional efforts, and a strategic, easily accessible location are crucial determinants of consumers’ choice of circumcision clinic. The practical implications of this research provide valuable insights for the management of Sunat Surgero Clinic in formulating more effective marketing strategies through price optimization, strengthening digital promotion, and selecting appropriate clinic locations. Theoretically, this study contributes to the growing body of healthcare marketing literature by emphasizing the importance of price, promotion, and location factors in influencing consumer decision-making behavior.